2013
DOI: 10.4236/abb.2013.42023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel oral iron chelator 1-(N-acetyl-6-aminohexyl)-3-hydroxypyridin-4-one (CM1) for treatment of iron overload in mice

Abstract: Desferrioxamine (DFO), deferiprone (DFP) and deferasirox (DFX) are promising effective iron chelatorsfor the treatment of iron overload in -thalassemia patients; nonetheless, their side effects have also been reported. 3-Hydroxypyridinone derivatives are being developed as a safer new chelator and in combined chelation therapy. We evaluated the iron-chelating activity of 1-(N-acetyl-6-aminohexyl)-3-hydroxypyridin-4-one (CM1) in iron-loaded C57BL6 mice. The feeding of a ferrocene-supplemented diet (Fe diet) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Instead, the greatest emphases have been placed on generating novel bi and tridentate chelators or modifying the properties of existing ligands. Over the years, several promising agents which vary in denticity, metal selectivity for Fe(III), toxicity, stability of the Fe-chelator complex and lipophilicity have been proposed and tested in several in vivo models including rodents, marmosets, dogs, and primates, with promising agents progressing to clinical trials [ 40 - 43 ]. Figure 5 shows the structures of a few previously reported iron chelators with potential clinical utility.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the greatest emphases have been placed on generating novel bi and tridentate chelators or modifying the properties of existing ligands. Over the years, several promising agents which vary in denticity, metal selectivity for Fe(III), toxicity, stability of the Fe-chelator complex and lipophilicity have been proposed and tested in several in vivo models including rodents, marmosets, dogs, and primates, with promising agents progressing to clinical trials [ 40 - 43 ]. Figure 5 shows the structures of a few previously reported iron chelators with potential clinical utility.…”
Section: Reviewmentioning
confidence: 99%
“…Importantly, CM1 showed efficacy in preventing lipid peroxidation, the underlying cause of cellular damage. Future studies are needed to determine clinical utility of this agent [ 43 ].…”
Section: Reviewmentioning
confidence: 99%
“…It is DFP analogue and is more lipophilic than DFP. In a previous study, we found that CM1 was able to bind both ferric and ferrous ions, and was also able to chelate plasma non-transferrin bound iron (NTBI), efficiently [8]. Moreover, we found that the CM1 was not toxic to peripheral blood mononuclear cells and liver cells in an in vitro study [9].…”
Section: Introductionmentioning
confidence: 91%
“…71 A closely related pyridinone has been developed by the Chiang Mai group (Thailand), namely CM1 ( Figure 1I). 72 The chelator is orally active in the rat and relatively nontoxic. CM1 is currently being subjected to systematic toxicity studies.…”
Section: Dialkylhydroxypyridinonesmentioning
confidence: 99%